Red/far-red and blue light-responsive regions of maize rbcS-m3 are active in bundle sheath and mesophyll cells, respectively. - Purcell, M (1995)
Leaves of the C4 plant maize have two major types of photosynthetic cells: a ring of five large bundle sheath cells (BSC) surrounds each vascular bundle and smaller mesophyll cells (MC) lie between the cylinders of bundle sheath cells. The enzyme ribulose bisphosphate carboxylase/oxygenase is encoded by nuclear rbcS and chloroplast rbcL genes. It is not present in MC but is abundant in adjacent BSC of green leaves. As reported previously, the separate regions of rbcS-m3, which are required for stimulating transcription of the gene in BSC and for suppressing expression of reporter genes in MC, were identified by an in situ expression assay; expression was not suppressed in MC until after leaves of dark-grown seedlings had been illuminated for 24 h. Now we have found that transient expression of rbcS-m3 reporter genes is stimulated in BSC via a red/far-red reversible phytochrome photoperception and signal transduction system but that blue light is required for suppressing rbcS-m3 reporter gene expression in MC. Blue light is also required for the suppression system to develop in MC. Thus, the maize gene rbcS-m3 contains certain sequences that are responsive to a phytochrome photoperception and signal transduction system and other regions that respond to a UVA/blue light photoperception and signal transduction system. Various models of "coaction" of plant photoreceptors have been advanced; these observations show the basis for one type of coaction.